Reservoir characterization of the Aldrich, Aldrich NE and Keilman North fields, Ness County, Kansas for potential exploration of sub-Mississippian formations - Leis, Jarred A. (Kansas State University, 2013)
Petroleum producing areas within the mid-continent region discovered in the first half of the 1900’s often ignored the potential of deeper horizons once hydrocarbons were discovered in shallower zones. In Ness County, Kansas the deepest horizon typically explored are Mississippian-aged rocks. One of the largest fields in Ness County is the Aldrich Field, first discovered in 1929. The Mississippian in this field contains an active water-drive, which was produced by an “open-hole” completion method. This precluded drilling deeper horizons. Although modern drilling and completion techniques allow drilling through and isolating water-drive reservoirs like the Mississippian, very few deep exploratory wells have been drilled in Ness County. Wells that penetrate sub-Mississippian horizons are typically drilled as disposal wells, along the flanks of the main structure. This study evaluates the potential of several sub-Mississippian formations to be hydrocarbon reservoirs. Drill cuttings from five wells that penetrate these formations were analyzed using a combination of petrographic microscope, Scanning Electron Microscope (SEM), and chemical methods. Reservoir quality porosity was observed in several sub-Mississippian zones. The presence of hydrocarbon staining was observed in the Viola samples of three wells, and the Arbuckle in one well. Staining was confirmed by EDS spectra under the SEM. The results of this study suggest a good potential of zones deeper than normally drilled to contain hydrocarbons in rocks with reservoir quality porosity. These zones were not drill stem tested in the Aldrich field, and structural advantage to these wells might be expected by drilling the apex of the trapping anticline to further evaluate the deeper horizons.
Keywords: Potential hydrocarbon exploration in Kansas; Geology (0372)